User Experience Evaluation of Botani Mobile Application using User Experience Questionnaire - Priandani, Nurizal Dwi; Sandy, Yohana Avelia; Sari, Nadia Roosmalita (Jurnal Teknologi dan Manajemen Informatika, 2023)
Agriculture is an important sector in Indonesia. Farming are how most people make a living within the population [1]. Currently, access to consult with agricultural experts is something that farmers don't have as a privilege. The combination of technology and agriculture needs to be developed to make it easier for farmers to consult. Botani Mobile Apps is an Android-based application that has been developed by the Faculty of Agriculture UB. The purpose of this application is to facilitate farmers in agricultural cultivation. User experience is how a person feels when using a product, system, or service [2]. User experience evaluation needs to be done to measure the success of a product design and to get user feedback for further improvement. One method of evaluating user experience is UEQ (User Experience Questionnaire). Evaluation of user experience of the Botanical mobile application using UEQ will be discussed in this study. Based on the results of the UEQ that have been carried out, the 26 questions asked had an average value of more than 1. After grouping the questions on the 6 UEQ Scale, the average results of calculation showed that all scales are in the green area. Based on UEQ characteristics, the highest scores were Attractiveness, Pragmatic and Hedonic qualities, respectively. All the results of the characteristic values were more than 1. Based on the Benchmark calculation, showed that the Attractiveness, Efficiency, Dependability and Novelty scales had good scale results and the Perspicuity and Novelty scales got above average scale results. Based on all the results of the UEQ evaluation, it can be concluded that the user experience on the BOTANI application is good.